Carnivalization: contributions to the study of the aesthetics of the grotesque - Silva, Matheus Victor [UNESP] (Editora Univ Pontificia Univ Catolica Rio Grande Sul-edipucrs, 2021)
The present article points to the relevance of Bakhtin's discussion about popular culture for the studies of the aesthetics of the grotesque. In this sense, we propose a discussion about Bakhtin's understanding of the grotesque from his study of the popular festival and carnival dialogism, in order to understand the manifestations of grotesque realism in the field of carnivalization, punctuating essential elements, although little discussed today in his theory, especially the renovating capacity and the cosmovisionary expansion operated by the grotesque aesthetics in artistic manifestations. In the following, we seek to contrast it with the most recent studies on the grotesque, such as those of Remi Astruc, seeking to demonstrate its timeliness and its potential contributions to this field of research.
Keywords: Grotesque; Carnivalization; Dialogism